Hubungan Self-Efficacy dengan Kedisiplinan Belajar Siswa SMK - Riska Elvira; Mudjiran Mudjiran (Jurnal Neo Konseling, 2019)
Discipline is something that is related to self-control of the form of rules by obeying the rules around. Discipline is a process or practice which of course individuals must experience or go through the process. Discipline is also shaped and developed through practice and education so that awareness and confidence in him are formed to do without coercion. In fact there are still many students who do not obey the rules that apply in school. That happens because the existence of students who are lazy learning because learning is not necessary and there are still students who are still not sure about the abilities possessed by him. This study aims to (1) describe students' self-efficacy, (2) describe student learning discipline, (3) test the significance of the relationship between self-efficacy and student learning discipline. This study uses a quantitative method with a correlational approach. The research sampling technique uses purposive sampling. The sample of this study was 155 students of SMK Negeri 10 Padang. The instruments used were (1) questionnaire selfefficacy, (2) student learning discipline. Questionnaire in this study uses a Likert scale model. Data analysis techniques used descriptive and correlational analysis techniques using computer program assistance Product and Service Solution (SPSS) version 20.0. The research findings show that (1) student self-efficacy is in the high category, (2) student learning discipline is in the discipline category, (3) there is a significant positive relationship between self-efficacy and student learning discipline with a correlation coefficient of 0.403 and a significant level 0,000.